Antimalarial drugs inhibit the replication of SARS-CoV-2: An in vitro evaluation. Issue 37 (September 2020) - Gendrot, Mathieu; Andreani, Julien; Boxberger, Manon; Jardot, Priscilla; Fonta, Isabelle; Le Bideau, Marion; Duflot, Isabelle; Mosnier, Joel; Rolland, Clara; Bogreau, Hervé; Hutter, Sébastien; La Scola, Bernard; et al.
Abstract: In December 2019, a new severe acute respiratory syndrome coronavirus (SARS-CoV-2) causing coronavirus diseases 2019 (COVID-19) emerged in Wuhan, China. African countries see slower dynamic of COVID-19 cases and deaths. One of the assumptions that may explain this later emergence in Africa, and more particularly in malaria endemic areas, would be the use of antimalarial drugs. We investigated the in vitro antiviral activity against SARS-CoV-2 of several antimalarial drugs. Chloroquine (EC50  = 2.1 μM and EC90  = 3.8 μM), hydroxychloroquine (EC50  = 1.5 μM and EC90  = 3.0 μM), ferroquine (EC50  = 1.5 μM and EC90  = 2.4 μM), desethylamodiaquine (EC50  = 0.52 μM and EC90  = 1.9 μM), mefloquine (EC50  = 1.8 μM and EC90  = 8.1 μM), pyronaridine (EC50  = 0.72 μM and EC90  = 0.75 μM) and quinine (EC50  = 10.7 μM and EC90  = 38.8 μM) showed in vitro antiviral effective activity with IC50 and IC90 compatible with drug oral uptake at doses commonly administered in malaria treatment. The ratio Clung /EC90 ranged from 5 to 59. Lumefantrine, piperaquine and dihydroartemisinin had IC50 and IC90 too high to be compatible with expected plasma concentrations (ratio Cmax /EC90  < 0.05). Based on our results, we would expect that countries which commonly use artesunate-amodiaquine or artesunate-mefloquine report fewer cases and deaths than those using artemether-lumefantrine or dihydroartemisinin-piperaquine. It could be necessary now to compare the antimalarial use and the dynamics of COVID-19 country by country to confirm this hypothesis.